Assessing the attitudes of hospitality students towards the use of a classroom response system (CRS) - Milholland, Eric Stanley, author; Miller, Jeff, advisor; Martin Gould, Susan, advisor; Hogler, Raymond, committee member (Colorado State University. Libraries, 2010)
A Classroom Response System (CRS) is a technology instructors can use to promote active learning. Researchers have shown a number of benefits of CRS use, including anonymous student response, better attendance, increased peer instruction, higher test scores, better grades, and the ability to use contingent teaching methods. Compared to traditional methods, contingent teaching allows instructors to gain real-time understanding of what students know and comprehend. Instructors then can use CRS based feedback to employ learner-paced instruction. Previous researchers focused on CRS use in disciplines like math and physics. A literature review did not locate any previous studies about using CRS in hospitality education. Regardless of the course studied, researchers found CRS was most effective when used as a tool to reinforce sound pedagogy. This study investigated the attitudes of hospitality students regarding the technology. The study was conducted over a three semester period, and was comprised of hospitality students (n=l 17) in an introductory food science course in which a CRS was used. Students responded to additional statements on standard course evaluation surveys. Students also wrote comments about their CRS experience in this class. Survey responses indicated students felt CRS encouraged discussion and participation, helped reinforce course concepts, and increased class enjoyment. Additionally, students suggested using CRS in more of their hospitality courses and in more courses university-wide. Students written responses indicated similar opinions as the surveys. Students indicated CRS helped them understand concepts, engage in discussion, and motivated them to attend. Others said using the device was fun and would recommend it to other students and for other classes. The results showed hospitality students have an overall positive attitude regarding CRS. This research indicated hospitality educators may want to use this technology to enhance instruction. As future versions of the technology evolve to become even more interactive, additional research should be conducted to see how CRS use will change in the future.
Covers not scanned.
Keywords: Hospitality industry -- Study and teaching (Higher); Student response systems